Lesson Learned Peralihan Mata Pencaharian Masyarakat Sebagai Ketahanan Terhadap Perubahan Iklim Kelurahan Mangunharjo - Tiara Citra Septiana (Department of Urban and Regional Planning, Diponegoro University, 2013)
The existence of catastrophic flooding, sea level rise, with the abrasion causes severe loss of farm land owned by the community. In fact, fishponds have been gotten a source of community life. If the pond area can no longer be processed, it will lead to socio-economic problems of society. Therefore, it required an effort of adaptation to adjust to changing environmental conditions due to the occurrence of the phenomenon of climate change. One of the adaptations made Kelurahan Mangunharjo’s community is to make the transition livelihood. In the transition process undertaken by livelihood there is definitely a learning community that is used as a stock of knowledge to switch to a new job.Further, the goal of this study is to find on lesson learn that can be taken from the transition in the Kelurahan Mangunharjo’s livelihoods that can be used for replication in other areas.The result of this study there are the distinguished based on the offender, which the offender learning process in the Kelurahan Mangunharjo can be divided into two parties, including individuals and groups. While, if it differentiated based on the learning process that is owned by Kelurahan Mangunharjo’s community, then there are two types of processes used, among others, through learning by doing and learning by interaction. Obstacles that still occurs today lies in the process of transfer of knowledge possessed by the community.Most people move to jobs that do not reach the level of education and skill levels are high,because they have a low knowledge and skill.